2022
DOI: 10.1021/acsomega.1c06958
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Morphologies of Anion-Exchange Membranes with Different Lengths of Fluorinated Hydrophobic Chains

Abstract: An anion-exchange electrolyte membrane, QPAF(C6)-4, polymerized with hydrophobic 1,4′-bis(3-chlorophenyl)perfluorohexane and hydrophilic (6,6′-(2,7-dichloro-9 H -fluorene-9.9-diyl)bis( N , N -dimethylhexan-1-amine) is physically flexible and chemically stable. The drawbacks are relatively large water swelling and lower OH – conductivity at higher water uptakes, which are considered to be due to the entanglement of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…This inhibits, rather than facilitates, microphase separation, ultimately leading to reduced mechanical properties and overall performance. 29,30 Thus, suppressing excessive WU and simultaneously achieving high ionic conductivity in polyarylene-type AEMs requires either inducing a structural modicationby introducing, graing, or hyperbranching spacer-type multi-cation conducting head groups, for exampleor adding physical or chemical crosslinkers. [20][21][22][31][32][33][34][35] The aforementioned approach, in which microphase separation between hydrophilic and hydrophobic domains is used to control the increase in WU and, thus, achieve improved mechanical and electrochemical properties, including ionic conductivity, is considered less suitable for polyarylene-based copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This inhibits, rather than facilitates, microphase separation, ultimately leading to reduced mechanical properties and overall performance. 29,30 Thus, suppressing excessive WU and simultaneously achieving high ionic conductivity in polyarylene-type AEMs requires either inducing a structural modicationby introducing, graing, or hyperbranching spacer-type multi-cation conducting head groups, for exampleor adding physical or chemical crosslinkers. [20][21][22][31][32][33][34][35] The aforementioned approach, in which microphase separation between hydrophilic and hydrophobic domains is used to control the increase in WU and, thus, achieve improved mechanical and electrochemical properties, including ionic conductivity, is considered less suitable for polyarylene-based copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…A simpler alternative for maximizing microphase separation between the hydrophilic and hydrophobic domains in polyarylene-based copolymers is to incorporate hydrophilic functional groups, such as ether linkers, into the polymer side chains or introduce uorine directly into the polyarylene structure as a hydrophobic group. 14,[29][30][31][36][37][38] In addition, ongoing research efforts address the use of polymer backbones with high free volume, combined with a rigid structure, to induce microphase separation in AEMs. [39][40][41][42][43][44][45][46][47] Free volume refers to the empty spaces between the polymer backbones due to the polymer components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the feasibility of our proposal set forth in Figure , functionalized Pi-POSS was prepared through decorating POSS nanoparticles with N -methylpiperidium groups, which were demonstrated to possess distinguished resistance against nucleophilic substitution and elimination under high temperatures and alkaline conditions. AEMs consist of the hydrophobic polymer backbone and hydrophilic cationic groups, which directly determine the dimensional stability, alkaline stability, and ion conductivity of AEMs. To improve the durability under alkaline conditions of AEMs, numerous studies on cationic groups and polymer backbones have been carried out. , Marino et al systematically investigated the alkaline stability of different kinds of quaternary ammonium (QA) groups . The results showed that the piperidinium-based cation certificates strong resistance against nucleophilic substitution and elimination under high temperatures and alkaline conditions …”
Section: Introductionmentioning
confidence: 99%